Travel distance and travel time using Stata: New features and major improvements in georoute - Sylvain Weber; Martin Péclat; August Warren (University of Neuchâtel, Institute of Economic Research (IRENE), 2021)
The user-written command georoute is designed to calculate travel distance and travel time between two addresses or two geographical points identified by their coordinates. Since its conception and description by Weber and Péclat (2017), the command has been gradually maintained and enriched. The new version of georoute presented in this article encompasses major improvements, such as the possibility to specify transport mode and departure time. The new features open the way to a multitude of more sophisticated research applications.
Keywords: C87; R41; 330; Stata; geocoding; travel distance; travel time